Proses dan Fase-Fase Perkembangan Psikologi Pendidikan - Dalimunthe, Putri Ani; Ardra, Imam Naufal; Pasaribu, Marian; Fitri, Ridho Ramadhani; Hasibuan, Try Yuana Dewi (Ikatan Dai Indonesia, 2023)
Psychology can be briefly defined as the science that studies human behavior and relationships between humans. Each phase that humans go through has special characteristics that differentiate it from other phases of growth or development. The psychological education phase starts from toddlers until they are adults. It takes the role of parents, teachers and the community environment to recognize their world and provide opportunities to develop their own potential. Apart from that, the learning model that best suits children's psychology is when facing various problems that link physical, cognitive, emotional and psycho-social. The method used in this research is the Library Research method, which is a library study, in this research the researcher looks for references in the form of literature. The psychological phases include: Phases during childhood aged 0-3 years, Pre-School Phase (3-6 Years), Age Phase 7-13 Years, Adolescent Phase, and Phase during Adulthood. The aim of this research is to describe the stages of development of educational psychology. This shows changes in human development at each phase.